Dual RNA processing roles of Pat1b via cytoplasmic Lsm1-7 and nuclear Lsm2-8 complexes - Vindry, Caroline; Stoecklin, Georg (Cell reports, 2017)
Pat1 RNA-binding proteins, enriched in processing bodies (P bodies), are key players in cytoplasmic 5′ to 3′ mRNA decay, activating decapping of mRNA in complex with the Lsm1-7 heptamer. Using co-immunoprecipitation and immunofluorescence approaches coupled with RNAi, we provide evidence for a nuclear complex of Pat1b with the Lsm2-8 heptamer, which binds to the spliceosomal U6 small nuclear RNA (snRNA). Furthermore, we establish the set of interactions connecting Pat1b/Lsm2-8/U6 snRNA/SART3 and additional U4/U6.U5 tri-small nuclear ribonucleoprotein particle (tri-snRNP) components in Cajal bodies, the site of snRNP biogenesis. RNA sequencing following Pat1b depletion revealed the preferential upregulation of mRNAs normally found in P bodies and enriched in 3′ UTR AU-rich elements. Changes in >180 alternative splicing events were also observed, characterized by skipping of regulated exons with weak donor sites. Our data demonstrate the dual role of a decapping enhancer in pre-mRNA processing as well as in mRNA decay via distinct nuclear and cytoplasmic Lsm complexes.
Gesehen am 25.07.2018